Statewide mental health training for probation officers: improving knowledge and decreasing stigma - Nikhil Tomar; Marilyn A. Ghezzi; Lauren Brinkley-Rubinstein; Amy Blank Wilson; Tonya B. Van Deinse; Stacey Burgin; Gary S. Cuddeback (BMC, 2017)
Abstract Background The large and growing number of probationers with mental illnesses pose significant challenges to the probationer officers who supervise them. Stigma towards mental illnesses among probation officers is largely unstudied and the effectiveness of training initiatives designed to educate probation officers about mental illness is unknown. To address these gaps in the literature, we report findings from a statewide mental health training initiative designed to improve probation officers' knowledge of mental illnesses. A single-group pretest posttest design was used and data about stigma towards mental illnesses and knowledge of mental illnesses were collected from 316 probation officers. Data were collected prior to and shortly after officers viewed a series of educational training modules about mental illnesses. Results Officers' knowledge of mental illnesses increased and officers demonstrated lower levels of stigma towards persons with mental illnesses as evidenced by scores on a standardized scale. Conclusion Mental health education can help decrease stigma and increase knowledge of mental illnesses among probation officers. More research is needed to assess the impact of these trainings on probationers' mental health and criminal justice outcomes.